2023
DOI: 10.3390/nu15102314
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Binding Protein of Lactobacillus casei Inhibits HT-29 Colorectal Cancer Cell Proliferation

Abstract: Many Lactobacillus casei strains are reported to exhibit anti-proliferative effects on colorectal cancer cells; however, the mechanism remains largely unknown. While there has been considerable interest in bacterial small metabolites such as short chain fatty acids, prior reports suggested that larger-sized molecules mediate the anti-proliferative effect of L. casei. Here, other possible ways of communication between gut bacteria and its host are investigated. LevH1 is a protein displayed on the surface of L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“… [ 110 ] Mucin binding protein-> Lactobacillus casei HT-29 • Anti-proliferative effects. [ 111 ] Cell wall – cytoplasmic extract, and nisin - Lactococcus lactis SW480 • Reducing cyclin D1 expression. • Anti-proliferative effect.…”
Section: Postbiotics and Crcmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 110 ] Mucin binding protein-> Lactobacillus casei HT-29 • Anti-proliferative effects. [ 111 ] Cell wall – cytoplasmic extract, and nisin - Lactococcus lactis SW480 • Reducing cyclin D1 expression. • Anti-proliferative effect.…”
Section: Postbiotics and Crcmentioning
confidence: 99%
“…It has been shown that mucin-binding protein obtained from Lactobacillus casei can inhibit proliferation in HT-29 cells [ 111 ]. It has been determined that cytoplasmic extract and cell wall of Lactococcus lactis , and nisin showed antiproliferative effects by reducing cyclin D1 expression in SW480 cells.…”
Section: Postbiotics and Crcmentioning
confidence: 99%
“…Probiotic-derived ferrichrome acts as a tumor-suppressive molecule via the c-Jun N-terminal kinase (JNK) signaling pathway against cancerous IECs to a greater extent than conventional chemotherapeutic drugs, including cisplatin and 5-FU [223]. The probiotic-derived P8 protein was found to eliminate metastasis [224] and suppress CRC growth via the inhibition of the Wnt signaling pathway [225], whereas mucin binding protein (MucBP) exhibits dose-dependent antiproliferative effects against HT-29 cells [226]. ↓ cell proliferation, extrinsic and intrinsic apoptosis induction, ↑ FasR and TRAILR1 expression (m2163)/ ↑ FasR, TNFR1, and TRAILR1 (m2386) [221] Mixirins (Bacillus sp.…”
Section: Other Bacterial Peptidesmentioning
confidence: 99%
“…HT-29 dose-dependent antiproliferative effect [226] Probiotic-derived P8 protein (Lactobacillus rhamnosus KCTC 12202BP) DLD-1…”
Section: Other Bacterial Peptidesmentioning
confidence: 99%